CHATGPT IN LEARNING ENGLISH, IS IT POSSIBLE? - Pagansa Putri, Yulia; Fitri Handayani; Riyen Permata (Universitas Mahaputra Muhammad Yamin, 2025)
The integration of artificial intelligence in education has sparked discussions on its effectiveness, particularly in language learning. This study examines students' perceptions of ChatGPT in English language learning using a quantitative descriptive approach. The research involved 63 students from the English Education Study Program at Mahaputra Muhammad Yamin University, Solok, during the 2023/2024 academic year, selected through a total sampling technique. Data were collected using a structured questionnaire consisting of 20 statements, administered via Google Forms. Students rated their responses on a five-point Likert scale ranging from